Reliability and quantile analysis of Pareto distribution - M. Shuaib Khan; M. Aleem; Zafar Iqbal; A. T. Pasha (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2009)
This paper presents the reliability and Quantile analysis of the Pareto distribution. The main interests are in the relationship between
Keywords: 330; Pareto distribution; Quantile analysis; percentile life